2000
DOI: 10.1074/jbc.275.16.11987
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Neural Wiskott-Aldrich Syndrome Protein in Neurite Extension in PC12 Cells and Rat Hippocampal Primary Culture Cells

Abstract: Neural Wiskott-Aldrich syndrome protein (N-WASP) is an actin-regulating protein that induces filopodium formation downstream of Cdc42. It has been shown that filopodia actively extend from the growth cone, a guidance apparatus located at the tip of neurites, suggesting their role in neurite extension. Here we examined the possible involvement of N-WASP in the neurite extension process. Since verprolin, cofilin homology and acidic region (VCA) of N-WASP is known to be required for the activation of Arp2/3 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 30 publications
(15 reference statements)
2
64
1
Order By: Relevance
“…The F-BAR/EFC domain induces plasma membrane invagination (8), suggesting an implication of membrane trafficking in neurite elongation. Surprisingly, knockdown of N-WASP also enhances neurite elongation in PC12 cells, which is in clear contrast to the previous report using dominant negative mutants of N-WASP (5). Meanwhile, knockdown of Toca-1 in cultured rat hippocampal neurons enhances axon branching a little but not axon elongation, whereas knockdown of N-WASP enhances both axon elongation and branching.…”
contrasting
confidence: 55%
See 2 more Smart Citations
“…The F-BAR/EFC domain induces plasma membrane invagination (8), suggesting an implication of membrane trafficking in neurite elongation. Surprisingly, knockdown of N-WASP also enhances neurite elongation in PC12 cells, which is in clear contrast to the previous report using dominant negative mutants of N-WASP (5). Meanwhile, knockdown of Toca-1 in cultured rat hippocampal neurons enhances axon branching a little but not axon elongation, whereas knockdown of N-WASP enhances both axon elongation and branching.…”
contrasting
confidence: 55%
“…It has also been reported that another putative dominant negative mutant of N-WASP, which has a mutation in the GBD and is unable to bind to Cdc42, also suppresses neurite extension in PC12 cells (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…p34Arc and p21Arc are concentrated in the actin filaments of NGF-stimulated growth cones from rat sympathetic neurons and PC12 cells (Goldberg et al 2000). Mutations in the VCA region of N-WASP block NGF-stimulated neurite growth in PC12 cells and hippocampal neurons (Banzai et al 2000), and an N-WASP mutant incapable of binding cdc42 also blocks neurite growth (Banzai et al 2000). The Drosophila version of Scar has a role in axonal development.…”
Section: Rho Gtpases: Organizers Of Actin Structuresmentioning
confidence: 99%
“…Recently Nck and phosphatidylinositol 4,5-bisphosphate have been shown to synergistically activate actin polymerization through N-Wasp in an in vitro actin pyrene assay (18). N-Wasp has also been shown to be essential in nerve growth factorstimulated neurite extension in PC12 cells, presumably through Arp2/3 complex-induced actin polymerization (19). Wasp's ability to promote the polymerization of actin has also been implicated in endocytosis (20).…”
mentioning
confidence: 99%